A disturbance observer based lumped-mass catenary model for active pantograph design and validation. Issue 6 (3rd June 2023) - Duan, Huayu; Dixon, Roger; Stewart, Edward
ABSTRACT: To understand and thus improve the dynamic behaviour of the railway pantograph-catenary system, researchers have developed a number of approaches to the catenary modelling. The Finite Element (FE) approach provides a high degree of accuracy, but at the cost of significant computing time. In contrast, researchers in active pantographs generally use relatively simple (and fast running) lumped-mass catenary models. This paper aims to improve on the models available for the design and validation of active pantographs. Firstly, the veracity of the classic lumped-mass model is assessed and a new catenary model is proposed, by augmenting the lumped-mass model with a dynamics-matched mass and a disturbance which can be found using a disturbance observer (DO). Open-loop, passive pantograph, results show that the proposed model can represent the dynamic behaviour exhibited in the FE catenary very well. Secondly, two PID controllers are designed for an active pantograph, and tested with the FE, classic and DO-based lumped-mass catenary models. It is shown that if a controller is validated on the classic lumped-mass model, the credibility will be low. In contrast, the new DO-based model is found to deliver more robust results, providing efficient simulations for active pantograph design and validation.